(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the status of adherence to antiviral treatment and some factors related to adherence to antiviral treatment of patients with chronic hepatitis B at Nghe An General Hospital in 2023. Subjects and methods of research: Cross-sectional description. The study subjects were patients diagnosed with chronic hepatitis B who were being managed and treated with antiviral drugs at the Tropical Diseases Clinic, Nghe An General Hospital. Results: The results of the study showed that the adherence to antiviral treatment of chronic hepatitis B patients at the Tropical Diseases Clinic, Nghe An General Hospital was 39.5%. Adherence to treatment was associated with marital status (p < 0.01) and distance from home to hospital (p = 0.05). Patients who had daily phone reminders to take hepatitis B antiviral drugs had higher adherence to treatment than patients who did not have daily phone reminders to take medication (p = 0.01). Conclusion: The rate of adherence to antiviral treatment assessed by the CEAT-HBV questionnaire was still low at 39.5%. Treatment adherence was associated with marital status, distance from home to hospital, and daily phone reminders for taking medication.